On the spectrum of the generalized Gelfand pair (u(p,q), h_n), p+q=n - Godoy, Tomás; Saal, Linda (Mathematica Scandinavica, 2009)
It is known that the spectrum of the Gelfand pair (U(n), H_n) is homeomorphic to the Heisenberg fan. In this paper after defining a suitable notion of spectrum, we prove an analogous result for the generalized Gelfand pair (U(p,q), H_n), p+q=n.